Produção de minitubérculos de batata (Solanum tuberosum L.) por aeroponia: densidade de plantio, dormência de minitubérculos, regimes de aspersão e cultivares - Balena, Leonardo (2019)
One of the major costs of a potato crop is its seed-tubers. The production of potato seeds through Aeroponics can reduce that cost. The goal of this work was to build and improve an experimental Aeroponic system for the production of potato seed-tubers and to evaluate the effect of planting density, aspersion regimes, cultivars and the dormancy of tubers obtained from this system. The first experimental Aeroponic system was built from February to March of 2018, aiming to evaluate the ideal plant density of cv. Ágata in the autumn season in Aeroponics. There is an increase on the yield of cv. Ágata to the increment of plant density up to 180 plants m-2, due to better light interception and allocation of photassimilates. The seedtubers from this experiment were allocated in a BOD chamber at 23° C in absence of light, aiming to understand the effect of the picking date and planting density in Aeroponics, on the dormancy of seed-tubers. It was concluded that the dormancy of seed-tubers varies in response to picking dates, but does not vary in response to planting densities, so that early harvested tubers have a longer dormancy period than those harvested later. The second experimental Aeroponic system was built from August to November of 2018, aiming to evaluate the effect of different aspersion regimes on cultivars Ágata and Atlantic. Four aspersion regimes were evaluated: 30 seconds of aspersion with 10-minute intervals; 30 seconds of aspersion with 3-minute intervals; 3 minutes of aspersion with 10-minute intervals; 3 minutes of aspersion with 3-minute intervals. The experiment was held in a randomized block design, in a split plot scheme with three repetitions. ‘Ágata’ had 57% higher multiplication rate and 27% lower average tuber mass than ‘Atlantic’. There was no difference among aspersion regimes, making the one with the lowest water usage (30 seconds and 10 minute intervals) more suited for the aeroponic system. It was concluded that the increase of plant density up to 180 plants m-2 increases the yield of cv. Ágata in the autumn crop, that the minitubers of late pickings have a shorter dormancy period, that different cultivars need different management practices, and that the shorter aspersion regime is more adequate for cultivation in this system.